In vitro antibacterial activity and in vivo therapeutic effect of Sesbania grandiflora in bacterial infected silkworms - Anantaworasakul P. (2017)
CONTEXT: Antibiotic resistance is a serious problem worldwide. Searching for new potential agents is, therefore, essential. The bark of Sesbania grandiflora (L.) Pers. (Fabaceae) has been used in folk medicine against various diseases. OBJECTIVE: To investigate the antibacterial activity of S. grandiflora bark and explore the therapeutic effect of the highest potent fraction. MATERIALS AND METHODS: Bacteria and healthy silkworms were exposed to three fractionated extracts (3.1-400 mg/mL) of S. grandiflora bark from hexane (HXF), chloroform (CFF), and ethyl acetate (EAF). The sets of bacteria were incubated at 37 °C while silkworms were kept at 27 °C for 24 h. To evaluate the therapeutic effect, silkworms infected with bacteria were exposed to the extracts (0.5-60 mg/mL) and incubated at 27 °C for 52 h. Qualitative analysis of the most potent extract was done using HPLC. RESULTS: EAF showed the highest activity with MIC against methicillin resistant Staphylococcus aureus (MRSA) and vancomycin resistant enterococci (VRE) of 1.6 and 0.4 mg/mL, respectively, and against Gram-negative Escherichia coli and Pseudomonas aeruginosa of 6.2 and 3.1 mg/mL, respectively. It is nontoxic to silkworms with LC50  > 400 mg/mL and has high therapeutic effect on infected silkworms with EC50 of 1.9 mg/mL. EAF consists of at least five major compounds, one of them is gallic acid. The activity of EAF is higher than the sum of individual activities of separated compounds. DISCUSSION AND CONCLUSION: These results suggest that EAF is a promising antibacterial extract, suitable for further investigation in rodents infected with drug resistant bacteria.